Utilization of Ozone and Kefir Whey Probiotics as a Green Technology in Coliform Removal in Health Care Facilities Wastewater - Fathar, Imam Rozali; Riani, Etty; Nurhasanah, Nurhasanah; Munawir, Abdillah (ASTONJADRO, 2023)
Health care facilities wastewater (HWW), such as hospital, is classified as domestic wastewater according to Minister of Environment and Forestry Regulation No.P68/2016. One of the important parameters is total coliform.  The disinfection process using chlorine is effective in reducing the number of coliforms, but it is indicated to cause residues and side effects for other microorganisms in the receiving water bodies. This research is an experimental study by utilizing ozone and probiotics from whey kefir to eliminate coliform bacteria, aiming to determine the strategy for choosing a method for removing total coliform bacteria in HWW using the Analytic Hierarchy Process (AHP) approach. Data processing used Expert Choice 2011 software and it was found that the criteria with the highest score were environmental aspects, namely 0.302 and the priority indicator being minimizing the risk of pollution with the highest score, 0.366. Determination of strategies in the process of eliminating coliform bacteria in HWW by making choices, between the use of chlorine, ozone and a combination of ozone and whey kefir probiotics with five criterias approach (environmental, technological, social, economic, and institutional). Ultimate priority by using ozon was chosen with a score of 0.449; use of ozone and probiotics is the second priority with a score of 0.316; and utilization of chlorine with a score of 0.235.